1988
DOI: 10.1073/pnas.85.17.6503
|View full text |Cite
|
Sign up to set email alerts
|

Influence of activating stimulus on functional phenotype: interleukin 2 mRNA accumulation differentially induced by ionophore and receptor ligands in subsets of murine T cells.

Abstract: We have investigated the linkage between CD4/CD8 phenotype and programing for specific responses in primary T-cell populations. In situ hybridization has been used to determine the frequency of cells competent to express the interleukin 2 (IL-2) gene after short-term stimulation with various polyclonal activators. The effects of the T-cell receptor ligands Con A and anti-CD3 monoclonal antibody were compared with those of a calcium ionophore that bypasses membrane receptors altogether. Induction with a calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…activation. E. Rothenberg et al originally reported that IL-2 gene induction, thought to be a specific marker of the T-!ymphocyte lineage, could be obtained by stimulation with the combination of a calcium ionophore and a phorbol ester in the presence of exogenously added IL-1, as early as at the double-negative stage of thymocyte development, before expression of the CD3-TCR complex (Rothenberg et al 1988(Rothenberg et al , 1990. We confirmed this result using FACS-purified cells from adult mice, and found, in addition, that IL-4 Is not yet detectable, but that small amounts of y-IFN can be produced by these CD3" cells (Table I).…”
Section: -The Ontogeny Of Lymphokine Gene Inducfbility In Developinmentioning
confidence: 99%
See 1 more Smart Citation
“…activation. E. Rothenberg et al originally reported that IL-2 gene induction, thought to be a specific marker of the T-!ymphocyte lineage, could be obtained by stimulation with the combination of a calcium ionophore and a phorbol ester in the presence of exogenously added IL-1, as early as at the double-negative stage of thymocyte development, before expression of the CD3-TCR complex (Rothenberg et al 1988(Rothenberg et al , 1990. We confirmed this result using FACS-purified cells from adult mice, and found, in addition, that IL-4 Is not yet detectable, but that small amounts of y-IFN can be produced by these CD3" cells (Table I).…”
Section: -The Ontogeny Of Lymphokine Gene Inducfbility In Developinmentioning
confidence: 99%
“…This might explain why no functional activity has been convincingly demonstrated FACS-purified subsets of adult thymocytes (I x 10^) were stimulated in microculture wells in the presence of irradiated dendritic cells (3 x lO'') as accessory cells and the combination of ionomycin (I //M) and PMA (1 ng/ml), plus or minus recombinant IL-1 (50 units/ml). Double-positive thymocytes were separated into high and low density by centrifugation on a percoil gradient (60%/70%), in mouse double-positive cells; in particular, no iymphokine secretion can be obtained after ionomycin and PMA stimulation (Rothenberg 1988). Recently, however, the minor subset of large cells among the double-positive thymocytes was reported to generate single-positive thymocytes upon intrathymic transfer, suggesting that this subset includes the minority of cells that will be selected for further maturation (Guidos et al 1989).…”
Section: -The Ontogeny Of Lymphokine Gene Inducfbility In Developinmentioning
confidence: 99%
“…Mature TcR+ thymocytes resemble peripheral T cells in their insensitivity to IL-1 when they are stimulated to produce IL-2 in response to TPA plus A23187. These chemical proxies for mediators of the phosphatidylinositol bisphosphate hydrolysis pathway may be able to induce IL-2 expression in all mature T cells, for they can also elicit high-level responses in most fresh peripheral CD8+ cells (24), cells which generally do not express IL-2 mRNA in response to either antigen or mitogenic lectins. In contrast, however, immature TcRdouble-negative thymocytes do not make IL-2 in response to TPA and A23187 at all unless IL-1 is present (35,36).…”
mentioning
confidence: 99%
“…The induction of either type of gene expression response depends on two steps: (i) the coupling of membrane receptors to intracellular signaling pathways and (ii) the effect of the resulting signaling mediators on transcription factors and/or on chromatin structure and RNA stability. It is known that the frequency of IL-2 producers in various populations and the levels of IL-2 mRNA that they accumulate are a function of the particular activating stimulus used (2)(3)(4). This suggests that the ultimate response phenotype of a T cell may not be heritably fixed but may be influenced by the type of external stimulus it receives.…”
mentioning
confidence: 99%